Nation-space and the transtemporal woodlands: The politics of the past in the heritagised narratives on forests in twenty-first century Finland - Mäkelä, Heidi Henriikka; Linkola, Hannu (Routledge, 2026)
Forests are regarded as culturally and economically significant emblems of Finnishness, especially in public speech. Finns have been described as having ‘a special relation to the forests and nature’, and the Finnish national identities, identity politics and society/space-relations have been constructed, expressed, and renewed through representations of forests. For example, the seemingly untouched lake-and-forest landscape has been at the very core of the Finnish national imagery for over 150 years despite the extensive and ongoing commercial exploitation of forests.
In the chapter, we analyse the multi-layered interplay between politics of past, nation-space, and forest environments, and examine the ways in which Northern forests are utilised and represented in the contemporary institutional heritagisation practices in Finland. We concentrate on the Wiki-Inventory for Living Heritage (WLH, 2016–) that is an open access participatory inventory platform administrated by the Finnish Heritage Agency. The WLH is a part of the Finnish implementation for the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage. We ask 1) how and why is a nation-state and/or nationality spatialised in forests in the heritagisation processes?; and 2) what kinds of (understandings of) temporal dimensions are being utilised and produced, and which political narratives do they serve?
We suggest that the relations between heritagisation and forests are brought forth through three inseparable narratives that interrelate the forest space, economic networks, people’s bodies, and heritagised understandings of Finnishness. These narratives perform 1) ‘mythic-ness’, 2) ‘modernity’, and 3) ‘new spiritual’ and ‘well-being’ dimensions of forests. Drawing from the studies on critical heritage, landscapes, and banal nationalism, we claim that the forest-related heritage practices constantly participate in producing social and spatial hierarchies of nations, functioning also as vehicles for exclusion, oppression, and cultural elitism. Furthermore, our study reveals that the intertwining of heritage and politics create new contexts and spatialities in which the mundane forms of national identities and human-environmental relations are being utilised, reshaped and reinforced by the transnational flows of neoliberal meaning-making.
The Routledge International Handbook of Heritage and Politics